The Role of Green Target Costing in Achieving Sustainable Competitive Advantage in Economic Units - Abidmuslim Hraiga, Raad; Najah Hadi Jaber, Ahmad; Abdulhassan Abbas, Ali (Journal of Economics and Administrative Sciences, 2025)
Research aims to determine the role of green target costing in enhancing and supporting sustainable competitive advantage in Iraqi economic units and to define the philosophical concepts of green target costing (GTC) and Sustainable Competitive Advantage (SAC). To achieve this, the research relied on an applied descriptive approach, applying it to an actual production environment, namely the "General Company for Fertilizer Industry - Southern Region in Basra," and relying on data for the year 2024. The research concluded that the application of GTC concepts in the reality of the Iraqi industry is in its early stages. One of the most important objectives of this application is to improve the efficiency of resource use and reduce waste, in addition to designing environmentally friendly products. This contributes to supporting and enhancing the sustainable competitive advantage of the economic unit. The research results show that the full application of the green target costing approach in the research sample created a gap between it and the cost, which amount which can be invested in environmental initiatives or improving competitive profitability. Therefore, the research recommended adopting the integrated GTC methodology in Iraqi national factories to support environmentally friendly national products and create a sustainable competitive advantage for them.